The Use of Cooperative Integrated Reading and Composition (CIRC) Method to Improve Students’ Reading Comprehension in Descriptive Text of The Seventh-Grade of SMP Negeri 3 Palembang - Amira Wulandari; Nike Angraini; Desi Suryatika (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
CIRC technique was effective to improve students reading achievement. This study aimed to whether there was any significant improvement in the students’ reading comprehension achievement in descriptive text after being taught using the CIRC method. the research method used in this study is a quantitative technique. in this study the authors applied experimental techniques because this school consisted of 11 classes for grade VII, the authors used 2 classes to be tested using experimental techniques so that it was easy to compare students' reading results. The sample of this research were class of VII.1 and VII.2 consisted of 32 students for each class. The data were collected by giving pre-test and post-test, also analyzed by using t-test (paired sample t-test and independent sample t-test) with the help of SPSS v.25 program. The result of this research showed that the p-value of paired sample was 0.000 which was less than 0.05, also the p-value of each aspects of reading in experimental group was less than 0.05, meaning that there was significant improvement in students’ reading comprehension achievement and students’ reading aspects after being taught by using CIRC method. The p-value of independent sample t-test was 0.000 which was less than 0.05, meaning that there was significant different between experimental and control groups, and the experimental students showed the positive responses and perception toward the teaching reading comprehension by using CIRC method. Therefore, the results of this research showed that the use of cooperative integrated reading and composition (CIRC) method improved students’ reading comprehension achievement in descriptive text of the seventh-grade of SMP Negeri 3 Palembang.